Effects of benznidazole:cyclodextrin complexes on the drugbioavailability upon oral administration to rats - Leonardi, Darío (2013)
Benznidazole (BZL) is the drug of choice for the treatment of Chagas´ s disease, a neglected parasitic infection. It is poorly soluble in water, which may have a direct impact into its bioavailability. Thus, the aim of this study was to evaluate the impact of stoichiometric and non-stoichiometric BZL:cyclodextrins (CDs) complexes on the bioavailability of BZL. The interaction of BZL with the CDs was investigated using differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X-ray diffractometry (XRD), phase solubility and dissolution studies. The oral bioavailability of BZL from these complexes was examined in rats. Both BZL solubility and dissolution increased by CD complexation. The inclusion complexes were found to improve the dissolution rate of BZL by 4.3-fold in comparison with BZL alone. Complexation of BZL with CDs derivatives increased its plasma concentrations when fed to rats, with AUC values increasing up to 3.7-fold and increasing 2.5-fold in comparison with BZL alone. It should be note that a remarkable increase in these parameters was observed in the case of the non-stoichiometric complexes. Thus, these CDs complexes could be used to efficiently deliver BZL in patients suffering from Chagas´ s disease.